FALSAFAH ALAM TAKAMBANG JADI GURU DALAM KEARIFAN TRADISI MASYARAKAT IBAN: SENI TATU : The Philosophy of Alam Takambang Jadi Guru in The Traditional Wisdom of The Iban Community: The Art of Tattoo - Mohammad Sufiyan, Ali Osman; Adilawati, A; Shaikh Azahar, Shaik Hussain (UNISZA, 2021)
This research explains about a local wisdom related to the Iban community of heritage, like tattoo’s. Symbolism towards the elements of nature is often used to express various ideas and meanings about their practices, culture and life. This research use a fully qualitative as a main approach . Data obtained through a qualitative approach using observational methods and interviews from informants that have expertise on tattoos. This research shows that the human mind is built from the nature, characteristics and forms of nature. Human learns from nature and create aesthetics while showing the ability to assimilate with nature so that there is a philosophy of nature being a teacher. It show that human mind is built from nature. This means that the evolving nature teaches people to think creatively and produce a creation that uses the elements of nature as a source of ideas. Every thing and event that happens in human life may not be inseparable from nature. The Iban community live in a natural environment. For them, nature is used as a teacher to solve all the problems that occur in their daily lives. Some individuals in Iban community, they have a skilled in creating work of arts that use the natural sources that exist in their environment. The aesthetic value of tattoos can also be seen in the motifs and designs produced by inspiring the source of nature. It shows that nature as a teacher or mind thinking in addition to the symbol of perseverance and psychology the of tattoo maker. Through nature, the Iban community produce creativity that uses natural sources in the tradition of tattoos that shows the local wisdom as well as their culture.